Obrzędy pogrzebu biskupa Rzymu : między requiem a radością płynącą ze zmartwychwstania Jezusa - Dzikowski, Andrzej (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The paper is to present both the historical and present-day regulation of canon law of the Catholic Church concerning the funeral of the pope. It focuses on the liturgical aspect of the exequial rites of the Roman Pontiff, shows theological background as well as the evolution of the ceremonies in the 20th century
Keywords: canon law; liturgy; funeral; pope